Notes on an endogenous growth model with two capital stocks i: The deterministic case - Dirk Bethmann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
This paper extends the class of AK models with an explicit solution to the case where there are two capital goods in the model. this extension holds, even if an external effect in the use of human capital in goods production ia assumed.
urn:nbn:de:kobv:11-10049282
Keywords: 330